2005
DOI: 10.1177/0091270005277196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Everolimus on Steady‐State Pharmacokinetics of Cyclosporine in Maintenance Renal Transplant Patients

Abstract: To investigate possible interactions of the novel immunosuppressant everolimus with cyclosporine, a multicenter, randomized, double-blind, placebo-controlled, dose-escalating phase I study was performed. Everolimus regimens (0.75-10 mg/d) were administered for 28 days to stable renal allograft recipients receiving the microemulsion form of cyclosporine. Steady-state cyclosporine profiles were assessed at baseline on day 0 (cyclosporine alone) and on day 21 with everolimus on steady state. By day 21, mean dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It was interesting to note that more subjects had higher C1 blood levels (54%) than C2 blood levels (46%) suggesting that C2 monitoring may result in exposure loss in some patients, if not all . In renal transplant patients who were maintained on a stable cyclosporine dose, it was shown that C2 cyclosporine concentrations (range: 681–1080 ng/ml) were at least 30% lower than the C max value (843–1621 ng/ml) which occurred with a median value of 1 h (range: 1–2 h) across most of the dosing cohorts during the pharmacokinetic evaluation days in the study . Falck et al .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of CsA levels with its own historic data in which MMF was coadministered to CsA [19] indicate a significant increase in c 2h levels when CsA is combined with RAD001 (P 5 .001), whereas differences between trough levels and AUC did not reach significance. In most clinical studies, pharmacokinetics of CsA appear not to be affected by RAD001 coadministration [18,20,21]. However, Kirchner et al [21] observed a nonsignificant 10% augmentation of CsA AUC after administration of a single, oral dose of RAD001.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not investigate the potential influence of ImTORs on CsA or TAC transport across Caco‐2 cells. However, several clinical studies previously reported that simultaneous administration of ImTORs with cyclosporine or TAC had no significant influence on the overall pharmacokinetic and blood levels of cyclosporine [13,41–43] or TAC [16].…”
Section: Discussionmentioning
confidence: 99%